Mentalna higiena družine - Kostnapfel, Janko (Obzornik zdravstvene nege, 1977)
The author considers the basic elements which form and build a sound family life and the ones bringing about its deconstruction and decomposition. The growth of a child from its earliest youth to the period of a well-formed personality is dealt with from the mental hygiene aspect. Educational habits are discussed and the relevance of a suitable emotional atmosphere in the famlly is pointed out. Special problems appearing with the minors are analysed, as well as the true sense of life and the influence of our present civilization level. Further on, the characteristical features of the present conjugal life are taken into consideration. The reader is instructed of the possibility of being advised by a psychiatrist. Finally, the author draws attention to the relation between the old and the young.